2011
DOI: 10.5604/15093492.933793
|View full text |Cite
|
Sign up to set email alerts
|

Body posture and trunk muscle activity in women following treatment of breast cancer

Abstract: Wstęp. Le cze nie ra ka pier si mo że po wo do wać nie pra wi dło we ukształ to wa nie krzy wizn przed nio-tyl nych krę go słu pa, co w kon se kwen cji pro wa dzi do za bu rzeń czyn no ścio wych mię śni tu ło wia. Ce lem pra cy by ło okre śle nie za le żno ści po mię dzy czyn no ścią mię śni tu ło wia a ty pem po sta wy cia ła ko biet le czo nych z po wo du ra ka pier si.Ma te riał i me to dy. 50 ko biet po le cze niu ra ka pier si. Śred ni wiek ba da nych wy niósł 61 la ta (±8,67), śred nia wy so kość cia ła … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
0
14
0
2
Order By: Relevance
“…There are, indeed, several studies in the literature proving the change in body posture in women after mastectomy. [7][8][9][10][11][12] These reports, however, mostly showed shoulder elevation and ipsilateral inclination of the trunk by using photogrammetry or Moiré topography. There is only one study in the literature evaluating the change in body posture based on bony structures in women after mastectomy in comparison with immediate breast reconstruction using special software analyzing digital images.…”
Section: Introductionmentioning
confidence: 97%
“…There are, indeed, several studies in the literature proving the change in body posture in women after mastectomy. [7][8][9][10][11][12] These reports, however, mostly showed shoulder elevation and ipsilateral inclination of the trunk by using photogrammetry or Moiré topography. There is only one study in the literature evaluating the change in body posture based on bony structures in women after mastectomy in comparison with immediate breast reconstruction using special software analyzing digital images.…”
Section: Introductionmentioning
confidence: 97%
“…Symmetry, natural shape, and proper size are biologically and esthetically important. An extremely large breast size may lead to difficulties in daily life and studies have demonstrated that physical weight and psychological factors may cause an altered skeletal posture (1)(2)(3). Moreover, many studies have reported that having both breasts is important in maintaining a center of gravity and stable posture (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…A realização desse tipo de tratamento para o câncer de mama promove, após a retirada da mama acometida ou de parte dela, leve transferência lateral de peso, principalmente em mulheres de mamas volumosas, que gera desalinhamento anormal da escápula e consequente assimetria do ombro. Dessa forma, determinadas compensações podem ser geradas, como, por exemplo, a elevação do ombro do lado operado, bem como alterações nas curvaturas da coluna vertebral [6][7][8][9] . Além disso, existem outras intercorrências cirúrgicas ou pós-cirúrgicas que podem afetar o bom alinhamento postural, como distúrbios de sensibilidade 10 , escápula alada, esclerose de vias linfáticas, linfedema e disfunção do ombro e da cervical, repercutindo negativamente na postura 6 .…”
Section: Introductionunclassified